"Deserve1093-4537S got [everything] to do with it": Unforgiven, revenge, and the revival of the western. Issue 2 (1st March 2017) - Joyce, Justin A.
Abstract : This essay weds conceptions of justice within Public Administration to the theme of revenge in the Hollywood Western, arguing that the revival of the genre in the 1990s reflects changes in the public conception of due process and equality before the law. The Western genre's evolution is illustrative of the way definitions of justice are socially, contextually specific. Unforgiven illustrates this shift because the violence in the film symbolizes the vengeance culture so anathema to American notions of procedural justice and explores shifting conceptions of justice through a 19th century allegory of injustice, the heart of which is the treatment of a person as property. This fantasy of the violent resolution of conflict is examined against Public Administration's insistence upon resolving competing conceptions of the good through peaceful, deliberative modalities.